2010
DOI: 10.1016/j.regpep.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 — Role as possible new potent regulator of food intake

Abstract: Nesfatin-1 is an 82 amino acid peptide recently discovered in the brain which is derived from nucleobindin2 (NUCB2), a protein that is highly conserved across mammalian species. Nesfatin-1 has received much attention over the past two years due to its reproducible food intake-reducing effect that is linked with recruitment of other hypothalamic peptides regulating feeding behavior. A growing amount of evidence also supports that various stressors activate fore- and hindbrain NUCB2/nesfatin-1 circuitries. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 44 publications
3
49
1
2
Order By: Relevance
“…One of the most important functions of nesfatin-1 is reducing food intake. It causes loss of appetite, less frequent hunger, and a sense of fullness (3)(4)(5)(6). It has been demonstrated that pancreatic beta cells colocalize with nesfatin/NUCB2 in the islets of both mice and rats, indicating the possible involvement of nesfatin-1 in the regulation of insulin secretion from pancreatic beta cells (7).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important functions of nesfatin-1 is reducing food intake. It causes loss of appetite, less frequent hunger, and a sense of fullness (3)(4)(5)(6). It has been demonstrated that pancreatic beta cells colocalize with nesfatin/NUCB2 in the islets of both mice and rats, indicating the possible involvement of nesfatin-1 in the regulation of insulin secretion from pancreatic beta cells (7).…”
Section: Introductionmentioning
confidence: 99%
“…However, although it was demonstrated that nesfatin-1 suppresses appetite via the regulation of NPY, CART and POMC, and that adiponectin regulates energy metabolism in association with NPY and POMC (6,7,20), the mechanisms underlying the changes in nesfatin-1 and adiponectin levels with advancing age have not been fully elucidated. The present study aimed to investigate the effects of aging on the plasma levels of nesfatin-1 and adiponectin.…”
Section: Introductionmentioning
confidence: 99%
“…Nesfatin-1, a recently described anorexigenic and satiety peptide, is secreted by different parts of the central nervous system (predominantly in the hypophysis and hypothalamus) and peripheral tissue such as the gastric mucosa, adipose tissue, and pancreas beta cells (4,8,(28)(29)(30). Experimental studies have revealed that cerebroventricular and peripheral nesfatin-1 injection in rats inhibited food intake (9,31).…”
Section: Discussionmentioning
confidence: 99%